1982
DOI: 10.1111/j.1570-7458.1982.tb03193.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF MIXED CROPPING ON SOME INSECT PESTS OF BRASSICAS; REDUCED BREVICORYNE BRASSICAE INFESTATIONS AND INFLUENCES ON EPIGEAL PREDATORS AND THE DISTURBANCE OF OVIPOSITION BEHAVIOUR IN DELIA BRASSICAE

Abstract: Intercropping brassicas with taxonomically unrelated plant species reduced infestations of the aphid Brevicoryne brassicae L. and the rootfly Delia brassicae (Bohé) by over 60% compared with those on brassicas grown in pure stand. Twice as many carabid and staphylinid predators of the immature stages of the rootflies were trapped on intercropped than on brassicas areas, but when they were excluded similar reductions in rootfly eggs occurred suggesting that predation was not an important factor suppressing root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…The third study mentioned (ICRISAT: see Bhatnagar and Davies [1982]) found both pest movement and natural enemies to be important in determining pest abundance patterns. Other recent studies that have examined both herbivore movement and enemycaused mortality have suffered from insufficient sampling to determine enemy activity (Andow 1983), or inadequate replication and experimental control (Tukahirwa & Coaker 1982). In one study (Salick 1983), numbers of enemies were insignificant.…”
Section: Tests Of the Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study mentioned (ICRISAT: see Bhatnagar and Davies [1982]) found both pest movement and natural enemies to be important in determining pest abundance patterns. Other recent studies that have examined both herbivore movement and enemycaused mortality have suffered from insufficient sampling to determine enemy activity (Andow 1983), or inadequate replication and experimental control (Tukahirwa & Coaker 1982). In one study (Salick 1983), numbers of enemies were insignificant.…”
Section: Tests Of the Hypothesesmentioning
confidence: 99%
“…While the two hypotheses are neither comprehensive nor mutually exclusive, they have been the focus of recent experimental work in agricultural settings (Bach 1980, Risch 1981, Tukahirwa & Coaker 1982, Andow 1983, Salick 1983. These studies provided little support for the enemies hypothesis.…”
mentioning
confidence: 99%
“…Many researchers have shown that the numbers of pest insects found on cruciferous crop plants are reduced considerably when the background of the crop is allowed to become weedy (Dempster, 1969;Smith, 1969;Dempster & Coaker, 1974;Smith, 1976), when the crop is intercropped with another plant species (O'Donnell & Coaker, 1975;Tukahirwa & Coaker, 1982;Ryan et al, 1980;Garcia & Altieri, 1992), or when the crop is undersown with a living mulch (Theunissen & Den Ouden, 1980;Theunissen et al, 1992;Finch & Edmonds, 1994;Theunissen et al, 1995). It has been suggested that when diverse backgrounds 'disrupt' (Vandermeer, 1989) insects from selecting otherwise-acceptable host plants, the action is mediated through (1) physical obstruction (Perrin, 1977), (2) visual camouflage (Smith, 1969;, (3) 'masking'of host plant odours (Tahvanainen & Root, 1972); (4) 'deterrent' ('repellent' -see later) chemicals (Uvah & Coaker, 1984), or through (5) the non-host plants altering the physiology of the host plants (Theunissen, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is also established that diversification might influence agroecosystems through various modes of action. Diversification can impede pests' host plant finding behaviour (Root, 1973;Wratten & van Emden, 1995;Finch & Kienegger, 1997;Finch & Collier, 2000), and it can affect crop yields directly ( Theunissen & den Ouden, 1980;Tukahirwa & Coaker, 1982). Diversification might also impinge on pests indirectly, through boosting their natural enemies, such as spiders.…”
Section: Introductionmentioning
confidence: 99%